A functionalized separator enables dendrite‐free Zn anode via metal‐polydopamine coordination chemistry. Issue 3 (5th October 2022) - Liu, Yanfen; Liu, Shude; Xie, Xuesong; Li, Zhicheng; Wang, Pinji; Lu, Bingan; Liang, Shuquan; Tang, Yan; Zhou, Jiang
Abstract: Designing a multifunctional separator with abundant ion migration paths is crucial for tuning the ion transport in rocking‐chair‐type batteries. Herein, a polydopamine‐functionalized PVDF (PVDF@PDA) nanofibrous membrane is designed to serve as a separator for aqueous zinc‐ion batteries (AZIBs). The functional groups (OH and NH) in PDA facilitate the formation of ZnO and ZnN coordination bonds with Zn ions, homogenizing the Zn‐ion flux and thus enabling dendrite‐free Zn deposition. Moreover, the PVDF@PDA separator effectively inhibits the shuttling of V‐species through the formation of VO coordination bonds. As a result, the Zn/NH4 V4 O10 battery with the PVDF@PDA separator exhibits enhanced cycling stability (92.3% after 1000 cycles at 5 A g −1 ) and rate capability compared to that using a glass fiber separator. This work provides a new avenue to design functionalized separators for high‐performance AZIBs. Abstract : A polydopamine‐functionalized PVDF (PVDF@PDA) nanofibrous membrane is designed as a separator for aqueous zinc‐ion batteries. The PVDF@PDA separator homogenizes the Zn‐ion flux distribution to achieve the dendrite‐free Zn deposition via the metal‐PDA coordination chemistry. Moreover, the PVDF@PDA separator inhibits the shuttle of V‐species. Benefiting from the separator, the Zn/NH4 V4 O10 full cell retains 92.3% capacity after 1000 cycles at 5 A g −1 .